(3GdQSGdI GdefHgI Ydi HYV CSQGQ GdbQBfs - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s
(3ChdgG (B:s
(3bGd CHh YHO dGdg eMeO Hf YeQ Hf GdMSjf GdQGRi QMeg Gddg gPg QSGdI YedJgG ai GdJfHjg Ydi HYV GdGSQGQ GdehOY ai ShQ GdbQGf GdYXje hGdaQbGf GdcQje s
(3BNQgG (B:s
(3hGYde Cf GaVd GdeYGQa eYQaI Gdgd JYGdi hGdEjeGf QFjS GdGYeGd GdUGdMI s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdhWfjI ai HjQhJ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs